LESSON LEARNT DARI PROSES PELATIHAN PERENCANAAN KEUANGAN KELUARGA - Hidayah, Nur; Kusmawati, Kusmawati; Rumasukun, Endang; Wahyuna, Wahyuna (Jurnal Abdimas Musi Charitas, 2023)
The problem of households in Brongkendik village is financial difficulty because they do not have a life goal. Several factors influence this, such as marriage customs, baby birth customs, "tomborgmagh" culture and other needs. "Tomborgmagh" is a culture of putting wealth to help families in preparation for marriage. The aim of this community service activity was to assist in preparing a financial plan based on a priority scale for the purpose of family life and welfare. This activity was carried out in the form of training for mothers of nutmeg production. The participatory action research method was the training method used, starting from the stages of determining life goals, budgeting, to the Tower arrangement game. Colored paper was the material used in the life goal setting stage, pencils and paper for the budgeting stage, and mineral water glasses to be used in the tower game. The results of this training showed that the nutmeg production women can develop a financial plan and they have a commitment to save